GAMBARAN KLINIS DAN RADIOLOGIS MENURUT KELLGREN AND LAWRENCE PADA PENDERITA OSTEOARTHRITIS GENU YANG BEROBAT JALAN DI POLOKLINIK ORTOPEDI RSU ANUTAPURA PALU TAHUN 2018 - amran, mukramin (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2019)
Osteoarthritis (OA) is a progressive and degenerative chronic musculoskeletal disease caused by thinning of the cartilage in the joint due to bone rubbing against each other. History of the patient's history, clinical picture of the physical examination and the results of the radiological examination are basic things to diagnose OA. Patient's complaints include joint pain which is a major complaint that brings the patient to the doctor, joint stiffness, crepitation, joint swelling, and changes in gait. Gait changes due to pain are found on a physical examination even though radiologically is still at an initial level. In addition it can be found that crepitus, swollen joints are often asymmetrical. The aim of this study was to determine clinical and radiological features by counselor and Lawrence of outpatient genotypes osteoarthritis patients in the rsu anutapura hammer orthopedic polyclinic in 2018. Descriptive research methods were conducted on 27 people with genital osteoarthritis who were treated at the orthopedic clinic in Anutapura Palu Public Hospital 2018. Consecutive sampling was used and data collection through interviews and observations in the form of pain, joint stiffness, crepitus, joint swelling and gait changes and radiological examinations based on Kellgren and Lawrence criteria. Data analysis using SPSS 25 with frequency distribution test. The results of the study were (1) based on the clinical picture in genu osteoarthritis patients pain (100%), pain accompanied by gait changes (70.37%), pain accompanied by joint stiffness (51.4%), pain accompanied by joint swelling (44, 4%), and pain with crepitus (37.0%). (2) based on radiology in patients with osteoarthritis genu with the highest grade 3 and 4 respectively (33.3%), grade 2 (29.6%), grade 1 (3.7%) and in grade 0 not found. Conclusion: found joint pain and a small portion of pain accompanied by crepitus, radiologists found in most grades 3 and 4 while grade 0 was not found.